Reservation And Virtual Tour Application Of Tourism Village in Banyuwangi Based On Android - Eka Mistiko Rini; Dianni Yusuf (Politeknik Negeri Malang, 2023)
Tourism development is the impact of changes in tourist interest in tourist destinations. The growing interest in tourism travel that wants to nature, interact, and learn the uniqueness of culture. Tourism Village is a form of integration between accommodation and supporting facilities presented in a community life structure that integrates with the rules and traditions that apply. To increase tourism potential in the Tourism Village promotion is required to attract travellers. Generally, traveller want to travel to the Tourism Village must come directly to the location to place an order. Therefore, we need an application regarding the information on Tourism Villages in Banyuwangi and ordering Android-based tour packages to bridge between visitors and Tourism Village managers. The application development method uses the waterfall framework by analyzing system design needs and testing. Application developed using a java-based programming language for the Android platform supported by the Android SDK and Android Studio as the development environment. This application aims to make it easier for the public and potential visitors to get information about Tourism Villages and to be able to order tour packages online. This application also makes it easier for Tourism Village managers to promote managed Tourism Villages